Taxation System for Maintenance of Flooding Building (Study Case is The Banger Polder Project) - Slamet Setioboro; Slamet Imam Wahyudi; Rick Heikoop (International Conference on Coastal and Delta Areas, 2015)
The Banger Polder Poject is a twinning project in which Indoensian authorities and Dutch parties work together to realize a polder system and an organization to operate and maintain this system in the Banger area in Semarang, Indonesia.( BPP, SIMA). Banger polder system is a part of the drainage system in the Middle Semarang area consisting of 524 ha which is made as a flood catchment area. This study aims to determine an appropriate concept to apply the taxation system for maintenence of the Banger Polder Project in accordance with the socio-economic conditions of Indonesian culture. The study focus on the implementation of the system of taxation in the case of ground water extraction. Most of Inhabitants Semarang are located in the lowlands take advantage of this by making the ground water wells dug (shallow) with an average depth of 3-18 m. The study use quantitative method to express the data in numbers and analysis SWOT method. In the study, the Netherlands (Water Board) was chosen as an example of implementation taxation in the field of water. So that, the goverment of Semarang can make some new rules or regulations in Taxation System.Keywords: Banger Polder, Flood, Taxation sytem, Underground water.